Conceptualising innovation as the foundational process of school transformation - Serra, Lídia; Alves, José; Soares, Diana (Portuguese Journal of Education, 2024)
Several studies have been developed about the difficulties of school change, the complexity of sustainability surrounding the process and the conservatism and resilience that mark the educational system. Innovation assumes centrality in the process of change because it is an important factor in the transformation of teachers' practices, a small link on a chain of changes that systemically pursues the school organisation. This narrative literature review conducted a historical-social approach to innovation. The purpose is to conceptualise the construct, following two dimensions: the ontological and the epistemological. Therefore, we propose a diagrammatic model and a synthetic definition of innovation that summarises the pluralist essence of educational innovation. The definition of innovation, considering its multidimensional nature and its dynamical and systemic features, follows five dimensions: scope; object; responsibility; focus; and course. This narrative literature review conducted a historical-social approach to innovation. The purpose is to conceptualise the construct, following two dimensions, the ontological and the epistemological. Therefore, we propose a diagrammatic model and a synthetic definition of innovation that summarises the pluralist essence of educational innovation. The definition of innovation, considering its multidimensional nature and its dynamical and systemic features, follows five dimensions: scope, object, responsibility, focus and course.